2021
DOI: 10.3390/cells10092350
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microorganisms and Parasites on Neuronally Controlled Drosophila Behaviours

Abstract: Like all invertebrates, flies such as Drosophila lack an adaptive immune system and depend on their innate immune system to protect them against pathogenic microorganisms and parasites. In recent years, it appears that the nervous systems of eucaryotes not only control animal behavior but also cooperate and synergize very strongly with the animals’ immune systems to detect and fight potential pathogenic threats, and allow them to adapt their behavior to the presence of microorganisms and parasites that coexist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 85 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Pathogen recognition is a central aspect of the innate immune response to eliminate invading microbes. Microbial sensing can occur at the level of chemoreception of exogenous cues (i.e., volatiles) via olfaction [45] , [46] , [47] , [48] , or detection of pathogen molecules once the invading microbe has gained access into the organism [3] , [49] . With respect to the latter, although lacking antibody production and other aspects of adaptive immunity, insects and other arthropods have evolved sophisticated innate immune systems that can be considered as quasi-adaptive [2] , [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen recognition is a central aspect of the innate immune response to eliminate invading microbes. Microbial sensing can occur at the level of chemoreception of exogenous cues (i.e., volatiles) via olfaction [45] , [46] , [47] , [48] , or detection of pathogen molecules once the invading microbe has gained access into the organism [3] , [49] . With respect to the latter, although lacking antibody production and other aspects of adaptive immunity, insects and other arthropods have evolved sophisticated innate immune systems that can be considered as quasi-adaptive [2] , [50] .…”
Section: Discussionmentioning
confidence: 99%
“…AMPs are important for regulation of normal functions of the insect brain, e.g., sleep and non-associative learning in Drosophila [ 25 , 26 ]. Results reported by Dissel et al showed that the transcript levels of metchnikowin ( Mtk ), drosocin ( Dro ), and attacin ( Att ) were differentially increased in glia, neurons, and the head fat body, respectively, in sleep-deprived flies.…”
Section: Amps In the Nervous Systemmentioning
confidence: 99%
“…Interestingly, the sensing of infections in the gut leads to the production of the Unpaired3 IL-6-like cytokine that metabolically reprograms the ensheathing glia and thereby affects their metabolic coupling to neurons. Thus, signaling from the gut leads to an enhanced avoidance of ECC15-laced food (Cai et al, 2021).This aspect of innate immunity has been recently reviewed (Montanari and Royet, 2021).…”
Section: Behavioral Immunitymentioning
confidence: 99%